2012
DOI: 10.1080/09593330.2012.676073
|View full text |Cite
|
Sign up to set email alerts
|

Struvite-based fertilizer and its physical and chemical properties

Abstract: This study describes a method to formulate struvite fine powder into pellets that are easy to spread on agricultural land. To evaluate the quality of produced pellets, some chemical and physical properties commonly measured for fertilizers were tested. The findings indicated that the salt index and heavy metal content ofstruvite pellets were significantly lower than those of commercial NPK fertilizers. In addition, the percentage of nutrient released from struvite pellets after 105 days was in the range of 9.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 22 publications
3
62
0
Order By: Relevance
“…Fine struvite crystals obtained from a reactor will be in the form of powder when dried later, which is difficult to spread on land using control from equipment because it is too light. 34 As supplied, this struvite could not find favor in agriculture. Struvite can be stored in a compact form, and it is easy and feasible to handle, transport, and apply, especially in granulated form.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Fine struvite crystals obtained from a reactor will be in the form of powder when dried later, which is difficult to spread on land using control from equipment because it is too light. 34 As supplied, this struvite could not find favor in agriculture. Struvite can be stored in a compact form, and it is easy and feasible to handle, transport, and apply, especially in granulated form.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Rahman et al 2 studied the P leaching rate in both struvite and fused superphosphate-urea-treated soil and found that P leaching was very slow during the first 2 weeks and then rapidly increased during the following weeks. Latifian et al 34 studied the release of nutrients in recovered struvite from wastewater and found that the total N, P, and Mg released in the distilled water after 105 days were in the ranges of 9.6− 23.2, 8.4−26.7, and 11.3−32.6%, respectively. These findings suggested that the dissolution and release of P resource from struvite might be slower than that of commercial fertilizer (i.e., CSP).…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Presence of calcium ions in a process system results that the product is a mixture of struvite and calcium phosphates(V) [8]. It essentially restricts its possible application as a mineral fertilizer [9].…”
Section: Introductionmentioning
confidence: 99%
“…Presence of calcium ions in a process system results that the product is a mixture of struvite and calcium phosphates(V) [8]. It essentially restricts its possible application as a mineral fertilizer [9].The research results concerning continuous struvite reaction crystallization process from synthetic animal breeding wastewater (SABW), of chemical composition similar to liquid cattle manure, are compared [1], [4]. Concentration of phosphate(V) ions in this solution was 0.208 mass %.…”
mentioning
confidence: 99%
“…The product should not contain too large an amount of impurities co-precipitated from the wastewater (Hutnik et al, 2013a). Such a solid product can be of practical use, e.g., as mineral fertilizer (NPMg) in agriculture (de-Bashan and Bashan, 2004;Latifian et al, 2012).…”
Section: Introductionmentioning
confidence: 99%